(untitled) (Scientific journal of the Fergana State University, 2023)
This article reveals the problems and special features of civilization of the world, traditional and anthropogenic character, describes the general characteristics, historical importance, distinctive features of each civilization. Moreover, this article gives an accurate representation of the world civilization on the example of Uzbekistan by citing the historical facts indicating the relationship of the peoples of Uzbekistan with the system of the world civilization, and also considerstheneedtodeepen the knowledge of people’s socio-cultural values.